Desain Kebijakan Pengentasan Kemiskinan Ekstrem di Kabupaten Lombok Barat - Purwadi; Yaarozatulo Harefa, Herman; Suhendra, Adi; Halik, Abdul; Santoso, Catur Wibowo Budi; Rosidah; Putra, Imam Radianto Anwar Setia; Apriani, Tini; Manoby, Worry Mambusy; Sutanto, Hari Prasetyo (Jurnal Bina Praja, 2023)
This study aims to analyze the design of extreme poverty reduction policies in West Lombok District. The design of the policy refers to the substance/content of the policies developed for the reduction/prevention of extreme poverty used by the regions. A case study research approach is used to explore the design of extreme poverty alleviation policies. The West Lombok Regency government's policy on poverty alleviation contains various local government programs synergized in accelerating the acceleration of extreme poverty reduction. In addition, it is in the form of efforts to assist the poor for a movement that is actualized in bridging aid recipients to get out of poverty immediately. The construction of extreme poverty reduction policies in West Lombok Regency adopts the concept of an innovation hub to accelerate cross-government programs that target basic services (health and education) in interventions for individual/family change as well as increasing the business capacity of community groups.